Stroke and pump thrombosis following left ventricular assist device implantation: The impact of the implantation technique - Nozdrzykowski, Michal; Bauer, Jessica-Marie; Schulz, Uwe; Jawad, Khalil; Bireta, Christian; Eifert, Sandra; Sandri, Marcus; Jozwiak-Nozdrzykowska, Joanna; Borger, Michael A.; Saeed, Diyar (Frontiers in Cardiovascular Medicine, 2023)
Objectives Several studies have shown the potential advantage of less invasive surgery (LIS) for left ventricular assist device (LVAD) implantation. This study aimed to determine the impact of LIS on stroke and pump thrombosis events after LVAD implantation. Methods Between January 2015 and March 2021, 335 consecutive patients underwent LVAD implantation using either conventional sternotomy (CS) or LIS technique. Patient characteristic was prospectively collected. All patients were followed up until October 2021. Logistic multivariate regression and propensity-matched analyses were performed to account for confounding factors. Results A total of 242 patients (F=32; 13.0%) underwent LVAD implantation with CS and 93 patients (F=8; 8.6%) using LIS approach. Propensity matching generated 2 groups, including 98 patients in CS group and 67 in LIS group. Intensive care unit stay for the LIS group was significantly shorter than in the CS group (2 [IQR, 2-5] days vs 4 [IQR, 2-12] days, p<0.01). There were no significant differences in the incidence of stroke events (14% in CS vs 16% in LIS group; p=0.6) or in pump thrombosis (6.1% in CS vs 7.5% in LIS group; p=0.8) between the groups. Hospital mortality in the matched cohort was significantly lower in the LIS group (7.5% vs 19%; p=0.03). However, 1-year mortality showed no significant difference between both groups (24.5% in CS and 17.9% in LIS group; p=0.35). Conclusions LIS approach for LVAD implantation is a safe procedure with potential advantage in the early postoperative period. However, postoperative stroke, pump thrombosis and outcome remains comparable to sternotomy approach.